Comparison of estimates of left ventricular ejection fraction using gated blood imagining - Steyn,Rachelle (Division of Nuclear Medicine, 2022)
Serial measurement of left ventricular ejection fraction (L VEF) using GBP imaging is an established technique for monitoring L VEF in patients undergoing chemotherapy with cardio-toxic medication and in patients after heart transplants. Oncologists at our institution decide that cardio-toxic chemotherapy should be discontinued if the L VEF decreases by 10%, or if a value of 50% is reached. In patients with baseline L VEFs of less than 50% but greater than 30% therapy will be discontinued if the L VEF decreases by 10% or if a value of less than 30% is reached. This is in accordance with the guidelines set out by the Oxford Textbook ofOncology.3 In patients who have had heart transplants, GBP studies are used to monitor L VEF. If there is a decrease in L VEF, cardiologists may decide to start glucocoricosteroids for rejection. It is therefore imperative that serial studies on an individual patient are comparable. There are two software systems used in our nuclear medicine department; the Siemens system and the Hermes system. In a pilot study we found large differences between the L VEFs calculated by the two systems. This is consistent with the consensus in the literature that different software programs for processing GBP studies cannot be used interchangeably.